Business and entrepreneurship for filmmakers : making a living as a creative artist in the film industry - Haine, Charles (New York : Routledge, 2020)
"This practical guide teaches readers the skills and business acumen required to build a career in the film industry from the ground up. While countless books and classes teach newcomers the creative aspects of the film industry, many fail to properly prepare readers for the reality of how to navigate a freelance film career today. From creating a business model, dealing with taxes and funding, finding and managing clients, networking, investing, cashflow, and planning for the long-term, Business and Entrepreneurship for Filmmakers provides real-world, pragmatic advice on navigating a freelance film career, whether you're a recent film school graduate looking to take the next step or a seasoned professional hoping to start a production company. Moreover, the skills taught here apply across the industry, from corporate media and commercials to music videos and feature films. Interviews with filmmakers, innovators, and business experts are included throughout the book to offer further expertise and examples"--
Taking care of yourself for long term survival -- Opportunities -- Having a plan -- The pitch deck and internal budgets -- Debt & investment -- Margins & cashflow -- Taxes, insurance, lawyers & retirement -- Bandwidth & hiring -- Portfolio and bidding -- Marketing, networking and promotion -- Clients and creative -- Representation -- Appendix: teaching.
OCLC-licensed vendor bibliographic record.
Keywords: Motion pictures -- Production and direction; Motion picture industry; PERFORMING ARTS / Film & Video / Direction & Production; PERFORMING ARTS / Film & Video / General